Fatty necrosis of falciform ligament due to torsion mimics falciform ligament cyst on MRI - Özdeniz, İlknur and Devay, Ali Önder and Özgan, Ediz Tevfik (The European Research Journal, 2018)
The falciform ligament which is a broad and thin peritoneal ligament, divides the left and right subphrenic compartments. Some pathologies of this ligament can be a rare cause of acute abdomen. Mostly its pathologies present a challenge for diagnose. In a case who was admitted with acute abdomen, we determined a fatty necrosis of the falciform ligament during surgery. This rare primary pathology of the falciform ligament mimics falciform ligament cyst on MRI, which is another rare pathology.